Antimicrobial ratings: the importance of importance. Issue 8 (17th June 2019) - Jordan, D
Abstract : Debate about antimicrobial resistance (AMR) in animals and the impact on humans is often inappropriately focussed on the crude amount of antimicrobials used in animals without deference to issues of 'intensity of use', 'quality of use' and especially the class of agents being administered. In the latter case, tools for helping to manage how the use of specific antimicrobial agents impact on the risk and consequences of antimicrobial resistance in humans have been available for almost two decades. These consist of antimicrobial ratings systems, which formally define the importance of each individual agent in human health by assigning them to a position on a graduated scale of 'importance' comprising up to four categories of risk. Until recently, these published ratings have only had a modest impact on antimicrobial stewardship at the frontline of medical and veterinary practice, although they will undoubtedly have a substantial influence into the future. This article considers the evolution of the available 'antimicrobial ratings systems' applicable to Australian and international settings and their pivotal future‐role in the educating of animal managers, policy makers and prescribers. Faithful application of these rating systems at all levels of decision making to do with antimicrobial use is now seen as central to the protection of animals, humans and economies from the scourge of AMR.